Are There Gender and Country of Origin Differences in Immigrant Labor Market Outcomes across European Destinations? - Alicia Adsera; Barry R. Chiswick (Institute for the Study of Labor (IZA), 2004)
The paper uses the 1994-2000 waves of the European Community Household Panel to conduct a systematic analysis of the earnings of immigrants as compared to native workers, in particular to test whether there is any systematic variation in the labor market performance of immigrants across gender related to duration in the destination, schooling, age at immigration, country of origin, or country of destination. We find a significant negative effect of immigrant status on individual earnings of around 40% at the time of arrival in the pooled sample, although the difference is somewhat smaller for women. Those differences, however, vary greatly across countries with migrants in Germany and Portugal faring best relative to natives, and those in Sweden, Denmark, Luxembourg or Spain the worst, particularly among non-EU born migrants. Gender differences are more important among those born outside the European Union, with women doing relatively better than men. Among men, those from Asia, Latin-America and Eastern Europe receive the lowest earnings. Latin- American and Eastern European women are at the bottom of the women?s distribution. Earnings increase with duration in the destination and the foreign born ?catch-up? to the native born, others variables being the same, at around 18 years in the destination among both men and women. Education matters more for women in terms of explaining earnings, whereas language skills are relatively more important for men.
Keywords: F22; J61; J1; 330; immigrants; earnings; gender; countries of birth and destination; language; Migranten; Lohn; Geschlecht; Ethnische Gruppe; Sprache; Schätzung; EU-Staaten